UA-MAC: An Underwater Acoustic Channel Access Method for Dense Mobile Underwater Sensor Networks - Chao Lv; Shuo Wang; Min Tan; Lan Chen (International Journal of Distributed Sensor Networks)
The long propagation delay and low data rate characteristics of acoustic communication attach many challenges to underwater wireless sensor networks. In this paper, a TDMA based underwater acoustic channel access method (UA-MAC) is proposed mainly to improve channel utilization in dense mobile underwater wireless sensor networks (MUWSN). In UA-MAC, the time slot of each node accessing to the acoustic channel is assigned according to a preverified template, which aims to minimize amount of slots so as to decrease the end-to-end delay. In addition, a piggyback based protocol is implemented to synchronize and schedule the network. The simulation results show that UA-MAC is much superior to common TDMA in throughput, channel utilization, and end-to-end delay especially in dense scenario. Based on the low-power low-cost underwater acoustic nodes we developed, the experiments were carried out to validate the proposed UA-MAC.